The role of Green Transformational Leadership and Green Product Innovation in Emerging Economies: Green Employee Behaviour and Green Human Resource Management as Intervening Variables - Rizal, Ach. Syaiful; Nuswantara, Dian Anita; Hariyati; Ali Alnajar, Ali Elazumi (Journal of Entrepreneurship and Business, 2024)
Purpose: This study is to offer a critical re-evaluation of the Green Transformational Leadership (GTL)–Green Product Innovation (GPI) relationship within SMEs in emerging economies, challenging the direct causality assumed in prior research. Theoretically, GTL, as a conceptual construct, lacks the mechanisms to produce a direct impact on GPI, a misconception widely propagated in earlier literature. As such, our study is to redirect such topical issues. In doing so, we also analysed green employee behavior (GEB) and green human resource management (GHRM) as intervening variables. Method: We distributed questionnaires into several SMEs operated in East Java, Indonesia. Result: Our empirical evidence strongly supports the proposed framework, suggesting no significant direct relationship between GTL and GPI and even showing a negative coefficient. However, when mediated by GHRM and GEB, the relationship becomes both positive and significant, indicating that these intervening variables are essential for realising the innovation potential of GTL. Furthermore, GTL partially fosters GHRM and GEB, while both GHRM and GEB positively influence GPI. These findings carry profound theoretical implications by refining the understanding of leadership’s role in sustainability practices and offering actionable insights for managers aiming to enhance green innovation through strategic HR and behavioural interventions.